From Insurance to Climate Change: Mapping Five Decades of Risk Preference Research in Agricultural Finance (1975-2025) - Aji, Joni Murti Mulyo; Hasanah, Julita; Rondhi, Mohammad; Suwandari, Anik; Rokhani, Rokhani; Yanuarti, Rizky; Damascena, Cindera Rosa (Food, Agriculture and Natural Resources - NETWORKS, 2025)
Risk preference in agricultural finance had become a critical research domain as farmers faced increasing exposure to market volatility, climate change, and systemic uncertainties. Research that specifically investigated risk behaviour and preference within agricultural finance remained fragmented and underexplored. Consequently, the intellectual structure, thematic development, and collaborative landscape of this emerging field had not yet been systematically mapped. The study aimed to identify the key contributors, dominant themes, and intellectual foundations. A bibliometric analysis was conducted using Biblioshiny 4.4.1 on 1,496 documents retrieved from the Scopus, covering the period 1975–2025 (24 April 2025). The results showed that publications expanded significantly after 2005, reaching a peak in 2023. Insurance, investment, and sustainability emerged as central research themes, while financial literacy, climate change, and pandemic-related risk appeared as emerging frontiers. Research on agricultural finance and risk preference developed into a multidisciplinary and globally interconnected domain, drawing insights from economics, environmental studies, and behavioral sciences. Future research on risk behaviour in agricultural finance should integrate behavioural insights with digital finance and climate risk modelling while expanding evidence from underrepresented regions such as Africa, Latin America, and Southeast Asia. Stronger linkages between farmer behaviour and policy innovations are essential to advance agricultural finance.